Comparison of muscle strength in male combat sport athletes - Busko, K. (Polish Journal of Sport and Tourism, 2016)
The aim of the study was to examine differences in muscle strength and topography between judoists, boxers, and taekwondo athletes. Material and methods. Thirteen judoists, 6 boxers, and 7 taekwondo athletes took part in the study. The maximal joint torque of the flexors and extensors of the elbow, shoulder, hip, knee, and trunk were measured under isometric conditions. Results. The absolute and relative joint torque was similar in the three groups except for the absolute strength of the right flexor of the shoulder between the boxers and the taekwondo athletes and judoists (p < 0.01). The sums of the relative joint torque and topography of the joint torque of the right and left upper extremity, lower extremity, and trunk were similar in the groups. A significant difference was observed in the topography of the joint torque of the right upper and lower extremity and of the trunk between the boxers and the taekwondo athletes and judoists (p < 0.01). The topography of the joint torque of the flexors and extensors of the right shoulder was significantly different between the boxers and the taekwondo athletes and judoists (p < 0.01). Conclusions. In martial arts, the training undergone by the athletes and their participation in competitions can be expected to affect their strength. The joint torque was similar in the combat groups examined in this study. Judoists and taekwondo athletes did not differ in muscle topography. Boxers differed from the other two groups only in the contribution of the flexors and extensors of the right shoulder, in the sum of the torques of the right upper and lower limb, and the sum of the torques of the trunk. These results may be due to the characteristics of the discipline and the training methods used